Fetal Biometry and Doppler Assessment of Pregnant Women with COVID-19 - Hiba Ahmed Suhail; Dalya Mudhafar Abdulrahman; Abeer Wali Ahmed (International Journal of Biomedicine, 2022)
Background: The world has changed radically because of the worldwide COVID-19 pandemic. SARS-CoV-2, a unique strain of large, enveloped single-stranded RNA viruses, that has spread around the world. The primary objective of this research was to assess the fetal growth velocity in pregnancies complicated by SARS-CoV-2 infection and those that were not. The secondary objective was to determine if SARS-CoV-2 infection may affect maternal and fetal Doppler readings. Methods and Results: A total of 250 pregnant women diagnosed with SARS-CoV-2 (Case group) were compared to 300 healthy pregnant women (Control group) in a prospective case-control study in Mosul from February 20 to October 20, 2021. Infections during pregnancy were detected and verified using the real-time reverse transcriptase-polymerase chain reaction (RT-PCR). All ultrasound exams were done from 24 to 40 weeks. Measuring parameters using Doppler ultrasonography included plasticity and resistive indices (PI, RI), as well as cerebroplacental ratio computed according to gestational age. Fetal development in utero was assessed by measuring biometric markers, such as parietal diameter, head size, belly circumference, leg length, and estimated fetal weight every four weeks. The US scans in the second and third trimester of pregnancy showed no evidence of congenital abnormalities (P=0.7047). There was a significant incidence of cesarean delivery (P=0.0000) and lower fetal activity at birth (P=0.0000) in the Case group, compared to the Control group. Anticoagulant treatment during pregnancy was not associated with an increased risk of postpartum hemorrhage in women of the Case group. Also, there were no significant differences in fetal biparietal diameter and femur length between groups in the second and third trimesters, and both fetal and maternal Doppler studies throughout the second and third (35-37 weeks) trimesters of pregnancy yielded no significant differences in the PI and RI indices.